Agenda Setting Redaksi RCTI Menyikapi Kontroversi Istilah ‘New Normal’ Dalam Mengatasi Pandemi Covid-19 - herik kurniawan kurniawan (Widya Komunika, 2021)
When the Indonesian government declared the Covid-19 pandemic, various efforts were made to contain the spread of the virus. The main effort is to change people's lifestyle that is safe from transmission of the virus because drugs and vaccines have not been found. The term that was coined by the government for this policy policy is 'new normal'. The government has carried out massive socialization through all its elements, including the media. The RCTI editorial team, through its news bulletin program, also socialized the government's efforts. As the editor of the media, RCTI makes new normal policies as part of the news management agenda. When controversy arises regarding the understanding of the term 'new normal', the RCTI editorial team consistently explains the new life habits that must be followed to prevent the spread of Covid-19. In the context of news related to the Covid-19 pandemic in Indonesia, controversy is not the focus of news, because it is not important to the public, so it is only used as ordinary news. This research uses qualitative methods with a content analysis approach. RCTI editors are more focused on the fundamental issue, namely how the pandemic can be ended.